Mechanism of Forced Summons against Witnesses Who Do Not Provide Information - Jacob Hattu; D. J. A. Hehanussa (Global Writing Academica Researching and Publishing, 2023)
Witness testimony is one of the valid proofs in the judicial process. Evidence has a very important position in the trial court examination process, because evidence contains provisions that contain outlines and guidelines regarding procedures that are justified by law proving the guilt of the accused, so by proving a criminal act a criminal sentence can be imposed. Therefore, the problem raised is what is the mechanism for summoning witnesses in criminal cases in Indonesia. To make a summons, the investigator must give a summons in writing. The deadline for summons with the time to attend the summons should be carried out with due observance of a reasonable deadline, which is no later than 3 (three) days received before the time to come to fulfill the summons. In practice, summons is conveyed to the summoned party in various ways, such as asking the summoned party to pick up the summons himself, entrusting it to a lawyer or the investigator delivering it directly to the summoned party. A summons based on a police report, a summons signed by the investigator or the investigator's superior as the investigator. The summons is submitted taking into account the sufficient grace period. If the second summons does not arrive at the stipulated time, the investigator issues a subpoena.